AN INSIGHT OF ANITALES APPS PERCEIVED BY DIGITAL STORYTELLING STUDENTS - Santiana, Santiana; Lesmana, Dede Surya; Marzuki, Abdul Gafur; Erizar, Erizar (Proceeding of International Conference on Islamic Education (ICIED); Vol 6 No 1 (2021): Proceeding of International Conference on Islamic Education (ICEID), 2021)
MALL (Mobile Assisted Language Learning) has been inextricably linked to education. Mobile learning is becoming increasingly common. As a result, a plethora of apps or smartphone applications has emerged to assist both teachers and students in improving the quality of learning. The introduction of Go Animate as a new method to facilitate mobile learning in the classroom was explored in the previous report. Using a phenomenological qualitative approach, the current study looks at another program called Anitales. Anitales is a program that allows you to make animated stories. Three university students who used Anitales in their Digital Storytelling Class were interviewed. The data was then analyzed using thematic analysis. The participants in the study had optimistic attitudes toward the use of Anitales. Anitales offered a variety of appealing features, which influenced students' emotions and motivation. Anitales worked with students to help them develop their imagination, writing, and speaking abilities.